2008
DOI: 10.2134/jeq2007.0427
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Two Soils Receiving Nitrogen Fertilizer and Swine Manure Slurry

Abstract: The interactive effects of soil texture and type of N fertility (i.e., manure vs. commercial N fertilizer) on N2O and CH4 emissions have not been well established. This study was conducted to assess the impact of soil type and N fertility on greenhouse gas fluxes (N2O, CH4, and CO2) from the soil surface. The soils used were a sandy loam (789 g kg−1 sand and 138 g kg−1 clay) and a clay soil (216 g kg−1 sand, and 415 g kg−1 clay). Chamber experiments were conducted using plastic buckets as the experimental unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 57 publications
5
54
1
Order By: Relevance
“…Although our incubation temperature was warmer than typical spring field conditions, N 2 O-emission peaks at the soil surface are primarily controlled by moisture-dependent diffusion-related processes rather than soil-temperature maxima (Lessard et al, 1996;Wagner-Riddle et al, 1997;Wagner-Riddle and Thurtell, 1998). The water-filled porosity of our sandy-loam soils maintained at field capacity would have been ≈ 54% (Jarecki et al, 2008), which is close to the critical threshold of 60% for denitrification often reported in the literature (Helgason et al, 2005;Rochette, 2008;Regina and Alakukku, 2010). Our incubation conditions should represent in situ spring soil-moisture conditions quite well and, hence, our estimated N 2 O fluxes from arable and native grassland soils should be indicative of what can occur in situ during the dormant vegetative period immediately after spring thaw prior to the growing season.…”
Section: Native Prairie Grassland Soil N 2 O Emissionmentioning
confidence: 99%
“…Although our incubation temperature was warmer than typical spring field conditions, N 2 O-emission peaks at the soil surface are primarily controlled by moisture-dependent diffusion-related processes rather than soil-temperature maxima (Lessard et al, 1996;Wagner-Riddle et al, 1997;Wagner-Riddle and Thurtell, 1998). The water-filled porosity of our sandy-loam soils maintained at field capacity would have been ≈ 54% (Jarecki et al, 2008), which is close to the critical threshold of 60% for denitrification often reported in the literature (Helgason et al, 2005;Rochette, 2008;Regina and Alakukku, 2010). Our incubation conditions should represent in situ spring soil-moisture conditions quite well and, hence, our estimated N 2 O fluxes from arable and native grassland soils should be indicative of what can occur in situ during the dormant vegetative period immediately after spring thaw prior to the growing season.…”
Section: Native Prairie Grassland Soil N 2 O Emissionmentioning
confidence: 99%
“…However, it is important to emphasize those agro-environmental problems which are not limited to the use of chemical fertilizers but also occur with manures and compost (Mitchell and Tu 2006). Both animal waste and chemical fertilizers have the potential of environmental pollution (McLaughlin and Mineau 1995;Jarecki et al 2008). Release of greenhouse gases (Flessa et al 2002;Jarecki et al 2008), ozone layer depletion (Ma et al 2007), global warming, and acid rain are reported as negative impacts of fertilizers (Vitousek et al 1997;Frink et al 1999).…”
Section: Potential Uses Of Pgpr and Rhizobiamentioning
confidence: 99%
“…Both animal waste and chemical fertilizers have the potential of environmental pollution (McLaughlin and Mineau 1995;Jarecki et al 2008). Release of greenhouse gases (Flessa et al 2002;Jarecki et al 2008), ozone layer depletion (Ma et al 2007), global warming, and acid rain are reported as negative impacts of fertilizers (Vitousek et al 1997;Frink et al 1999). Microbial inoculants, such as PGPR, are promising components for integrated solutions to agro-environmental problems because inoculants possess the capacity to promote plant growth, enhance nutrient availability and uptake, and support the health of plants (Barea et al 1998;Dobbelaere et al 2001;Hodge et al 2001;Bonfante 2003;Vessey 2003;Kloepper et al 2004;Han and Lee 2005;Weller 2007;Adesemoye et al 2008).…”
Section: Potential Uses Of Pgpr and Rhizobiamentioning
confidence: 99%
“…Four gases of immediate concern are Hydrogen Sulfide (H 2 S), Carbon Dioxide (CO 2 ), Ammonia (NH 3 ) and Methane (CH 4 ) which, at elevated exposure levels, generate health issues ranging from mild irritation to death for both animals and humans (Thu et al, 1997). Additionally, gases such as Dinitrogen Oxide (N 2 O), Methane (CH 4 ) and Carbon Dioxide (CO 2 ) are associated with greenhouse effects (Jarecki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%